Andean resistance in Lima at the beginning of the Spanish occupation: The evidence of Huaca Bellavista - Santa Anita - Gómez Torres, Roxana (2022)
In Huaca Bellavista, located in the district of Santa Anita, just over 2 km from Puruchuco- Huaquerones, important evidence of the first years of the arrival of the Spaniards in Peru has been recovered. According to the investigations carried out, these correspond to the remains of inhabitants who participated in the taking of Lima in the year 1536. This article presents the results of the analysis of six bodies impacted by projectiles from firearms and another three with impacts by Andean weapons. Among the personages that show these evidences of interpersonal violence are adults and children. These findings, together with the one from Puruchuco Huaquerones, are the only material evidence so far reported on the use of firearms in the Andean territory at the beginning of the Spanish occupation and corroborate the early historical sources on these events in our history.